Do injunctive or descriptive social norms elicited using coordination games better explain social preferences? - Robert J. Schmidt (University of Heidelberg, Department of Economics, 2019)
We experimentally study the relationship between social norms and social preferences on the individual level. Subjects coordinate on injunctive and descriptive norms, and we test which type of norm is more strongly related to behavior in a series of dictator games. Our experiment yields three insights. First, both injunctive and descriptive norms explain dictator behavior and recipients' guesses, but perceptions about descriptive social norms are behaviorally more relevant. Second, our findings corroborate that coordination games are a valid tool to elicit social norm perception on the subject level, as the individuals' coordination choices are good predictors for their actual behavior. Third, average descriptive norms on the population level accurately predict behavior on the population level. This suggests that the elicitation of descriptive social norms using coordination games is a potentially powerful tool to predict behavior in settings that are otherwise difficult to explore.
urn:nbn:de:bsz:16-heidok-271750
Keywords: C70; D70; D91; 330; injunctive social norms; descriptive social norms; social preferences; coordination